Pirates : a nonfiction companion to Pirates Past Noon - Osborne, Will.; Osborne, Mary Pope.; Murdocca, Sal (New York : Random House, 2001)
Jack and Annie discuss the interesting facts about pirates, living on a sailing ship, pirate treasures, and why people became pirates.
" A Stepping Stone Book"
Includes index.
006-009
680
680
Accelerated Reader AR
Keywords: Pirates